PENGARUH KESADARAN WAJIB PAJAK, PEMAHAMAN PERPAJAKAN DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK - Ratnawati, Juli; Rizkyana, Sefita (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
Taxes are people’s contributions for the state treasury which are used for the construction of facilities either at the central or regional governments. This research purpose to knowing is the taxpayer awareness, understanding of taxpayers, and public services of tax authorities on taxpayer compliance in the Karangayar area. The type of data used in this study is primary data, data collection used by questionnaire. The sample in this study amounted to 100 taxpayer respondents, whose sample collection used accidental sampling method. The data analysis method used in this study is multiple linear regression test. The results of this study indicate that awareness taxpayer, taxpayer understanding, and the taxpayer services have a significant effect on taxpayer compliance.